Consumer Trust and Availability of Islamic Financing Against Decision to Choose Murabahah Financing Products at the Selling Business Unit Buy Used Motorbike in Banda Aceh City - Kautsar, Muhammad; Syahputra, Hendra; Elfida, Cut (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2024)
Consumer confidence and the availability of financing products are the most important aspects before making a purchase decision, especially with a murabaha contract. The field phenomenon shows that many people do not understand the murabaha contract, so the trust generated is also still lacking. these two factors, namely consumer confidence and the availability of financing products, are related to consumer decisions. This study was conducted with the aim of knowing the effect of consumer confidence and the availability of financing products on purchasing decisions for murabaha financing products for buying and selling used motorbikes in Banda Aceh City. This research is quantitative research, conducted through distributing questionnaires to 92 respondents using the LeMeshow formula with a simple random sampling technique, represented by 115 respondents. The results showed that partially and simultaneously, consumer confidence and the availability of financing products had a significant effect on the decision to choose murabaha financing products in the used motorcycle buying and selling business unit in Banda Aceh City.